KNOWLEDGE MANAGEMENT: A PATHWAY TO ORGANIZATIONAL COMPETITIVENESS IN TODAY’S ECONOMY (Journal of the Management Sciences, 2024)
Knowledge is considered as the organizational power and it is the real asset of organizations when it comes to surviving in this competitive business environment. Without knowledge, organizations would find it very challenging to effectively respond to the everchanging market needs to maintain its competitiveness and therefore the concepts of knowledge management is becoming a necessity for any organization whether it is large, medium or small; even though their managing approach can be different. The study explores knowledge management as a pathway to organizational competitiveness in today’s economy but specifically seeks to ascertain the effect of knowledge sharing on employee creativity. The study employed descriptive survey design and the population of the study is 349 staff. Taro Yamane formula was used to ascertained the sample size of 230. Structured questionnaire was used to elicit vital information from the respondents. Simple regression analysis was employed in the test of hypothesis. The result revealed that knowledge sharing has significant effect on employee creativity. High degree of knowledge sharing supports individual employee’ learning process and thus enhances an individual’s creative skills, another building block of individual creativity. The study therefore recommends that organizations/companies should foster/ encourage knowledge sharing to enable employees generate novel and creative ideas by accessing diverse knowledge and information and interacting with people who have variety of expertise.
Keywords: Knowledge Management, Knowledge Sharing, Competitiveness, Employee Creativity.